Influence of Job Motivation on Effective Job Performance of Library Personnel in Universities - Quadri, Ganiyu Oluwaseyi; Obaseki, Grace Morenike; Bakare, Dorcas Oluwabunmi (International Journal of Knowledge Content Development & Technology, 2024)
This study investigated the influence of job motivation on job performance of library personnel in university libraries in Oyo State, Nigeria. Descriptive survey research design type was used for the study. The population of the study consisted of 164 library personnel in university libraries in Oyo State. An adapted questionnaire was used as the instrument for data collection. The data collected were analyzed using both descriptive and inferential statistics. PPMC were used for hypotheses testing at a 0.05 level of significance. The findings of the study revealed that the level of job performance of library personnel among university libraries in Oyo State was high ( =2.85) and that the level of job motivation (promotion, compensation, conducive work environment) of library personnel among the sampled universities was also high ( =2.77). More so, the findings of the hypothesis disclosed that there is a significant and positive relationship between job motivation (p= 0.029 < 0.05) and job performance of library personnel among universities in Oyo State. It was recommended that library leadership should make provision for motivational ingredients that can serve as an encouragement for the library personnel to enhance the level of their job performance.